Effectiveness “Alliance with stress” educational program on the level of knowledge, attitudes and practices of strategies to cope with stress in the freshmen nursing, section A, of the Faculty of Health Sciences, Universidad Peruana Union Lima - Villa Casapino, María Elena (2019)
Objective: The objective of the study was to determine the effectiveness of the “Alliance to stress” educationalprogram, level of knowledge, attitudes and practices of strategies to cope with stress in the first year students ofnursing, section A, of the Faculty Health Sciences, Universidad Peruana Union, Lima headquarters. Methods: Alongitudinal study of cut, pre experimental design with pre-test and post-test to one group. The sample consistedof 27 freshmen nursing, who participated in an educational program organized in 15 theoretical and practicalsessions for four months. Results: The results before applying the program show that 96.3% of students showeda low level of knowledge on strategies for coping with stress, 92.6% had positive attitudes and negative attitudes7.4%, and in relation to practices, 85.2% had moderately favorable practices and 11.1%, favorable practices.After the program, 96.3% had a level of knowledge between medium and high, 77.8% had positive attitudes, while 22.2%, negative attitudes; and practices regarding the medium remained favorable and favorable increased14.8%. The analysis by T test for related samples considering α = 0.01, reported for the level of knowledge (t =10,987, p = 0.000), to attitudes (t = 2408, p = 0.023) and practices (t = 0.581, p = 0.566). Conclusions: “Alliancewith stress” educational program was effective in the level of knowledge on strategies for coping with stress,unlike attitudes and practices where there were no significant variations